Contribuciones de metodologías basadas en el juego a la enseñanza del inglés (2023)
This article presents a literature review about the contributions that two active game-based methodologies, game-based learning and gamification, had made to the learning of English as a foreign language during a period of five years between 2019 and 2023. To this end, fifty research reports from different academic repositories were selected; their analysis involved the design of some matrices to identify, examine and synthesize the data. As a result, it was established how these methodologies have contributed to raise levels of motivation and engagement in EFL classrooms, and the way they have fostered communicative skills, which are key for the learner’s academic process. These findings demonstrate that these methodologies cause an integral effect; they promote the meaningful learning of English while being immersed in a joyful environment that allows the implementation of digital and analog tools in online and face-to-face contexts.